KETERAMPILAN MEMBACA PESERTA DI KELAS 6 SDIT ENTER - Nurhasanah, Ana; Adya Pribadi, Reksa; Saraswati Binti Fatman, Susi (STKIP Subang, 2021)
Reading skill is one that must be possessed by students. The purpose of this study was to determine the reading skills of students at SDIT Enter Serang-Banten. This study uses a descriptive method with a qualitative approach to data collection techniques carried out by direct observation and documentation studies. The subjects of this research are students. Based on the results of observations and research conducted by researchers, it is found that there are some students who are not fluent in reading and have not been able to determine the main idea and describe a reading text. With this problem, the researcher provides a solution by using the anti-creation guide model, group method and literacy board media with reading texts that can improve students' reading skills.